From a Co-Mo precursor to 1H and 1T Co-promoted MoS2: exploring the effects of gas pressure - Prabhu, M. K.; Groot, I. M. N. (Frontiers in Physics, 2023)
The work presented in this paper makes use of the high-pressure in situ imaging capabilities of the ReactorSTM to demonstrate that single layer 1T Co-promoted MoS2 can be directly synthesized without the use of any intercalating agents by applying highly reducing conditions during the growth. In this work, we have sulfided a CoMo nanoparticle precursor supported on Au(111) using a H2:CH3SH gas mixture at 1 bar and imaged the crystallization process in situ using the ReactorSTM. We have observed that at low temperatures ( 500 K), an intermediate disordered CoMoSx phase is formed which crystallizes into metallic single-layer 1T Co-promoted MoS2 slabs at temperatures close to 600 K. We also show that semiconducting 1H Co-promoted MoS2 slabs synthesized under sulfur-rich conditions using a vacuum physical vapor deposition process, do not transform into their metallic 1T counterparts when exposed to the same reducing gas pressures and temperatures, thus, demonstrating the importance of the highly reducing conditions during the crystallization process for inducing the formation of the metastable 1T phase. XPS spectra of the 1T Co-promoted MoS2 slabs indicate a sulfur deficiency of up to 11 % in the top layer S, suggesting the likely role of sulfur vacancies in the formation of the 1T phase.